Seismic fluid identification using a nonlinear elastic impedance inversion method based on a fast Markov chain Monte Carlo method - Zhang, Guang-Zhi; Pan, Xin-Peng; Li, Zhen-Zhen; Sun, Chang-Lu; Yin, Xing-Yao (Petroleum science, 2015)
Elastic impedance inversion with high efficiency and high stability has become one of the main directions of seismic pre-stack inversion. The nonlinear elastic impedance inversion method based on a fast Markov chain Monte Carlo （MCMC） method is proposed in this paper, combining conventional MCMC method based on global optimization with a preconditioned conjugate gradient （PCG） algorithm based on local optimization, so this method does not depend strongly on the initial model. It converges to the global optimum quickly and efficiently on the condition that effi- ciency and stability of inversion are both taken into consid- eration at the same time. The test data verify the feasibility and robustness of the method, and based on this method, we extract the effective pore-fluid bulk modulus, which is applied to reservoir fluid identification and detection, and consequently, a better result has been achieved.